2017
DOI: 10.12788/jhm.2933
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Inpatient Telemetry Utilization Through a System-Wide Electronic Health Record Change and a Multifaceted Hospitalist Intervention

Abstract: Although electronic telemetry ordering changes can produce decreases in hospital-wide telemetry monitoring, a multifaceted intervention may lead to an even larger decline in utilization rates. Whether these changes are durable cannot be ascertained from our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…One of these reduced laboratory costs by 16%, while the other reduced daily charges for telemetry monitoring in an academic medical center by 69%. 45,46 A third study, by Schwartz and coauthors, examined myriad low-value services and found overall reductions in low-value services among organizations participating in the Medicare accountable care organization program, though heterogeneity in reductions in individual types of services. For example, while low-value cancer testing dropped by 2.4% relative to the mean, preoperative services experienced no statistically significant change in use.…”
Section: Clinician-focused Intervention Componentsmentioning
confidence: 99%
“…One of these reduced laboratory costs by 16%, while the other reduced daily charges for telemetry monitoring in an academic medical center by 69%. 45,46 A third study, by Schwartz and coauthors, examined myriad low-value services and found overall reductions in low-value services among organizations participating in the Medicare accountable care organization program, though heterogeneity in reductions in individual types of services. For example, while low-value cancer testing dropped by 2.4% relative to the mean, preoperative services experienced no statistically significant change in use.…”
Section: Clinician-focused Intervention Componentsmentioning
confidence: 99%
“…Highly reliable, precise, user-friendly, and cost-effective clinical alarm systems are critical to efficient functioning of health-care facilities [1][2][3]. Despite tremendous progress over the past few decades, the "perfect solution" remains elusive, with focus being placed primarily on clinical indications and appropriateness of use for the existing equipment and monitoring frameworks [3][4][5][6]. Beyond the concept of "false alarm," suboptimal implementation of clinical monitoring systems can have much more profound and potentially dangerous consequences [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…14 Other studies have shown that multicomponent interventions including education, process change, routine feedback, and financial incentives decrease telemetry utilization. 7 As in the Najafi et al study, our intervention was not significantly resource-intensive and only involved modifications to the EHR. Directly engaging the primary provider for the patient to consider discontinuation of telemetry orders also supported active-provider decision-making for patients whose telemetry order exceeded the standard duration for a specific indication.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several studies have tried different approaches to address these shortcomings including provider education, routine feedback, provider incentives, and modifications to electronic health record (EHR) telemetry orders. These studies have demonstrated that multifaceted approaches do in fact lead to more appropriate telemetry utilization and duration of use, [7][8][9][10] but may require more resources and time to complete. Other studies have shown that changes to the EHR with reminders about discontinuing telemetry via pop-up dialog boxes or automatic telemetry discontinuation after a set time period, without provider education or incentives, were enough to encourage appropriate telemetry ordering and increase timely telemetry discontinuation.…”
Section: Background and Significancementioning
confidence: 99%